Pengaruh Kepemimpinan Tranformasional dan Perilaku Inovatif Terhadap Kinerja Pegawai - Arisman; Sopiah (PT FORMOSA CENDEKIA GLOBAL, 2022)
In the transformational leadership style, a leader gives freedom to his employees or employees to work and assumes that they are partners and not subordinates. The existence of innovative behavior shown by employees, where employees can innovate to work, complete work properly and correctly is a behavior that is currently widely used in small, medium and large companies. This behavior will encourage employees to give maximum results and show good performance and provide all the potential that exists for the progress of the company. In the literature review conducted by almost all the journals used, it shows that transformational leadership is leadership that increases employee motivation, satisfies employee needs and treats them as whole human beings. This leadership pattern will encourage employees to give their best at work, employees will bring out their best abilities and in the end, employee performance will increase. Transformational leadership patterns will not only encourage better employee performance, but will also create employees who are broad-minded, able to think outside their daily habits and increase innovative thinking to complete their work. The combination of leaders who apply transformational leadership patterns and innovative behavior leads to maximum performance and benefits the company.